Comparative Framing Analysis of Malaysia Online Media Reporting on Cybercrime - Sun Jing Wen; Tan Poh Ling (Faculty of Leadership & Management, 2024)
E-Proceeding of 4th International Conference on Islam, Media and Communication (ICIMac 2024): “Communication & Digitisation in Madani Society”/ Muhammad Raqib Mohd Sofian, , Siti Suriani Othman, Safiyyah Sabri, Osama Kanaker & Ihab Ahmed Ra’uf Awais. 5th March 2024 Organized by : Faculty of Leadership & Management